KERANGKA MODEL KONSEPTUAL PENERIMAAN APLIKASI PLAGIARISM CHECKER UNTUK PENINGKATAN KUALITAS KARYA ILMIAH - Ulpah Andayani (UIN Imam Bonjol Padang, 2020)
Improving the quality of scientific papers has become a concern of many circles, especially by universities. Various universities in Indonesia have now subscribed to applications or technology-based systems that are used to detect the level of similarity of a paper with other existing works. This paper aims to provide a conceptual framework model for application acceptance or a plagiarism checker system based on a review of various relevant writings and literature. The model of academic integrity and belief in technology is considered to have significance for the acceptance of the academic community towards the implementation of the plagiarism checker application or system. This model is based on reading and analyzing various relevant writings or literature. Based on these results, universities need to instill the importance of having academic integrity and providing technical skills to increase the acceptance of the academic community towards the application of plagiarism checkers to improve the quality of the scientific work produced.